2008
DOI: 10.1002/ptr.2557
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fenugreek 4‐hydroxyisoleucine on liver function biomarkers and glucose in diabetic and fructose‐fed rats

Abstract: Fenugreek (Trigonella foenum graecum L) is a plant traditionally used for the treatment of diabetes. It contains an unusual amino acid, 4-hydroxyisoleucine, demonstrated to have insulinotropic and antidiabetic properties in animal models. Here we examine the effect of 4-hydroxyisoleucine on liver function and blood glucose in two rat models of insulin resistance, fructose-fed rats and streptozotocin-induced diabetes type 2. In fructose-fed rats, levels of glucose and liver damage marker aspartate transaminase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 21 publications
1
34
0
1
Order By: Relevance
“…Increased glucose tolerance, increased insulin sensitivity, reduced hepatic glucose production, increased phosphatidylinositide-3 kinase (PI3K), reduced fasting insulin [93] Hamsters Decreased serum triglycerides, decreased serum total cholesterol, decreased free fatty acids, increased HDL:TC ratio [95] Type II diabetic rats Decreased blood glucose, increased serum HDL, decreased alanine aminotransferase, decreased aspartate aminotransferase [100] C57BL/db/db mice Decreased blood glucose, decreased serum triglycerides, total cholesterol and LDL, increased serum HDL [101] Type I diabetic rats Decreased blood glucose, decreased serum total cholesterol, decreased serum LDL, decreased serum triglycerides, increased serum HDL [102] The molecular mechanism of action of 4-OHIle has been studied using cell culture models. In rat muscle cells, it has been observed that glucose uptake and GLUT-4 translocation to the plasma membrane were increased after 16 h exposure to 4-OHIle [103].…”
Section: Experimental Results Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Increased glucose tolerance, increased insulin sensitivity, reduced hepatic glucose production, increased phosphatidylinositide-3 kinase (PI3K), reduced fasting insulin [93] Hamsters Decreased serum triglycerides, decreased serum total cholesterol, decreased free fatty acids, increased HDL:TC ratio [95] Type II diabetic rats Decreased blood glucose, increased serum HDL, decreased alanine aminotransferase, decreased aspartate aminotransferase [100] C57BL/db/db mice Decreased blood glucose, decreased serum triglycerides, total cholesterol and LDL, increased serum HDL [101] Type I diabetic rats Decreased blood glucose, decreased serum total cholesterol, decreased serum LDL, decreased serum triglycerides, increased serum HDL [102] The molecular mechanism of action of 4-OHIle has been studied using cell culture models. In rat muscle cells, it has been observed that glucose uptake and GLUT-4 translocation to the plasma membrane were increased after 16 h exposure to 4-OHIle [103].…”
Section: Experimental Results Referencementioning
confidence: 99%
“…4-OHIle resulted in decreased plasma triglycerides, total cholesterol (TC), and FFAs, and a simultaneous increase by 39% of the HDL-C:TC ratio. Haeri et al (2009) [100] determined the effect of 4-OHIle on streptozotocin-induced diabetic and fructose-fed rats. Liver function markers and glycaemia improved after an eight-week treatment at a dose of 50 mg/kg.…”
Section: Pharmacological Effects Of 4-hydroxyisoleucine (4-ohile)mentioning
confidence: 99%
“…Furthermore, other contributing factor might the chemical constituents found in the defatted seed fractions (Ribes et al, 1987); alkaloid rich fraction (Shani et al, 1974;Puri et al, 2002), and compounds such as diosgenin (Pasich et al, 1983;Farnsworth and Marles, 1995), trigonelline (Mishkinsky et al, 1967), coumarin (Khurana et al, 1982), nicotinic acid (Duke, 2001), and 4-hydroxyisoleucine (Narender et al, 2006;Haeri et al, 2009) isolated from fenugreek seeds extract.…”
Section: Discussionmentioning
confidence: 99%
“…Several such claims were confirmed experimentally. Various pharmacologically active compounds such as alkaloids (Shani et al, 1974;Duke, 2001;Zhao et al, 2003;Satheeshkumar et al, 2010); flavonoids (Adamska and Lutomski, 1971;Shang et al, 1998); tannin like phenolic compounds (Duke, 2001); polyphenols (Kaviarasan et al, 2008); steroids (Taylor et al, 1997); saponins (Dawidar et al, 1973;Pasich et al, 1983;Gupta et al, 1986;Yoshikawa et al, 1997;Sauvaire et al, 1998;Murakami et al, 2000;Raju et al, 2004;Yang et al, 2005); dioscin; free amino acids (Duke, 2001); an unusual amino acid 4-hydroxyisoleucine (Haefelé et al, 1997;Sauvaire et al, 1998;Haeri et al, 2009); coumarin derivatives (Khurana et al, 1982); lipids (Beutler and Der Marderosian, 2002); phospholipids (Xu et al, 1992); mucilaginous fibers (Srichamroen et al, 2009); vitamins; and minerals have been isolated from fenugreek seeds (Farnsworthand Marles, 1995;Duke, 2001). Some of the steroidal saponins isolated from fenugreek seeds, were found to stimulate growth-hormone release in rat pituitary cells (Shim et al, 2008), while higher phenol and polyphenols contents of fenugreek controlled oxidative damage (Kaviarasan et al, 2007;Dixit et al, 2008;Kaviarasan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…4-Hydroxyleucine, a novel amino acid from fenugreek seeds increased glucose stimulated insulin release by isolated islet cells in rats, mice and humans [10,16,48,49] . Trigonella foenum-graecum has been observed to cause glucose-induced insulin release in vitro and in vivo [6] .…”
Section: Trigonella Foenum-graecum (Leguminosae)mentioning
confidence: 99%